2012
DOI: 10.1177/0002716212461748
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Survey Nonresponse

Abstract: Nonresponse is a prominent problem in sample surveys. At face value, it reduces the trust in survey estimates. Nonresponse undermines the probability-based inferential mechanism and introduces the potential for nonresponse bias. In addition, there are other important consequences. The effort to limit increasing nonresponse has led to higher survey costs—allocation of greater resources to measure and reduce nonresponse. Nonresponse has also led to greater survey complexity in terms of design, implementation, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 31 publications
(24 reference statements)
0
90
0
2
Order By: Relevance
“…Third, as noted earlier, the response rate of the survey was rather low, although it compares favorably with the response rates of many other large-scale telephone surveys conducted in recent years, particularly those involving Latinas/os. To be sure, a growing literature has demonstrated that low response rates need not imply biased results (Groves 2006;Massey and Tourangeau 2013;Peytchev 2013). Nevertheless, it would be ideal to have a higher response rate in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Third, as noted earlier, the response rate of the survey was rather low, although it compares favorably with the response rates of many other large-scale telephone surveys conducted in recent years, particularly those involving Latinas/os. To be sure, a growing literature has demonstrated that low response rates need not imply biased results (Groves 2006;Massey and Tourangeau 2013;Peytchev 2013). Nevertheless, it would be ideal to have a higher response rate in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Unit nonresponse was the subject of two National Research Council reports and a special issue of a major social science journal (National Research Council 2011, 2013Massey and Tourangeau 2013). The Office of Management and Budget (2006) has set a target response rate for federal censuses and surveys, and recommends analysis of nonresponse bias when the unit response rate is less than 80 percent.…”
Section: Rising Unit Nonresponse Ratesmentioning
confidence: 99%
“…Third, response rates suggest that the findings should be interpreted with caution with regard to representativeness, although response rates should not be used as the only measure of representativeness. 44 This study employed probability sampling to obtain a representative sample, but lower response rates were countervailing forces; researchers must consider the juxtaposition of representative sampling methods with actual participation, loss to follow-up and other factors. [45][46][47] In assessing representativeness, one useful comparison is that between study estimates and those from other sources, such as the 2012 NYC Community Health Survey (CHS).…”
Section: Discussionmentioning
confidence: 99%